2008
DOI: 10.1111/j.1752-7325.2007.00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Rural Latino Immigrant Caregivers' Conceptions of Their Children's Oral Disease

Abstract: Objective: The aim of this study was to examine Latino immigrant caregivers' explanatory models of the causes of early childhood caries (ECC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 9 publications
6
37
0
1
Order By: Relevance
“…The need is evident for a state-wide concerted effort to reach Spanish speaking families regarding the availability of fluoride varnish and how they can obtain it for their children. These findings are similar to other surveys or focus groups of Latinas in the U.S. indicating that the lack of knowledge and understanding about fluoride and it benefits is widespread [9,12,13]. This lack of knowledge suggests strongly that all groups who interact with these families--medical and dental providers, preschool groups such as WIC and Head Start staff--must be educated and subsequently spend time on the topic with their Spanish speaking patients.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The need is evident for a state-wide concerted effort to reach Spanish speaking families regarding the availability of fluoride varnish and how they can obtain it for their children. These findings are similar to other surveys or focus groups of Latinas in the U.S. indicating that the lack of knowledge and understanding about fluoride and it benefits is widespread [9,12,13]. This lack of knowledge suggests strongly that all groups who interact with these families--medical and dental providers, preschool groups such as WIC and Head Start staff--must be educated and subsequently spend time on the topic with their Spanish speaking patients.…”
Section: Discussionsupporting
confidence: 70%
“…Similar outcomes were found among rural Latino immigrant caregivers in California [9]. Additionally, several focus groups have been conducted among English speaking, low income Maryland parents of young children regarding dental caries prevention, however none has been reported among Latinas on this topic [10].…”
Section: Introductionsupporting
confidence: 57%
“…It is apparent that parents knew that sugars in the diet can cause dental caries, but were not aware of hidden sugars and their effects. In other studies, urban Mexican American and immigrant Latino mothers rarely recognized cariogenic food beyond candy and demonstrated uncertainty as to how exactly bottle feeding is detrimental to oral health (Hoeft et al, 2010;Horton & Barker, 2008). In another study, ninety eight percent of children had juice in bottles or sippy cups (Southward et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…However, poor knowledge was noted in Wu-Han, China (Petersen & Esheng, 1998) where only 42% of mothers knew that dental caries is caused by sugar while only 39% of mothers in Romania (Petersen et al, 1995) knew that dental caries is caused by sugar. In most studies, few could identify the diet with hidden sugars (Hoeft et al, 2010;Horton & Barker, 2008;Petersen et al, 1995). Prolonged duration of bottle use put a population of low income Latino preschool children at increased risk for ECC (Hoeft et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Early dental visits result in fewer restorative needs and therefore reduced cost for treatment later in life [20] and also more positive views about dentists and dental visits [21]. Some researchers have found that parents might have poor knowledge and practice of effective preventive measures [22], might not understand the relationship between the child's diet and oral disease or might accord low value to primary teeth or might not recognize early signs of oral health problems in their children [23] [24]. However, the majority of this study participants knew that children have two sets of dentition and that the first set is important and should be taken care of.…”
Section: Discussionmentioning
confidence: 99%